Saúde mental de estudantes do ensino superior durante a pandemia de covid 19: passos e descompassos desta travessia. - Muniz, Lidiane Monte Lima (2024)
The Covid-19 pandemic has had many impacts on the mental health of the general population. In view of this, university students, in particular, had their study flows interrupted or modified, generating psychological suffering in this part of the community. Therefore, this study aims to analyze the mental health situation of higher education students in Ceará, during the pandemic. This is a descriptive and exploratory study, with a cross-sectional design. It was part of a broader investigation, carried out from July 6 to September 10, 2020. The study in question sought to identify signs and symptoms related to the mental health of university students during social isolation and quarantine. The main results found were that most of the students involved in the study were female (61.4%), Fortaleza and Sobral were the municipalities with the most active collaboration: (28.1%) and (20.4%). Regarding changes in teaching methodology, 1,492 (40.4%) remained in the remote format, 1,305 (35.4%) with distance learning commitments, and 784 (21.2%) had activities canceled. It was also evident that the average Positive Well-Being was highest for married people, followed by widowers, then those in a stable relationship and divorced, being lowest for singles. Mental health, overall, and in the main dimensions of Positive Affect and Emotional Bonds, as well as Positive Well-Being, was better in private institutions. The state of Mental Health, in general, tends to improve with increased satisfaction in relation to participation in pedagogical activities promoted by the institution during the period of isolation. Therefore, the state of Mental Health, globally, tends to increase with better conditions and access to the internet, during social isolation, while it tends to decrease with the increase in concern about continuing the course in person. In view of this, mental health, in general, in both dimensions and in all primary dimensions, except in Dim2 - Emotional Ties, was better for those who were not afraid of being infected by the coronavirus, worse for those who had already been infected, and intermediate for those who were afraid of being infected. Consequently, this circumstance, although unusual, also reflects that a significant portion of the sample was dissatisfied with the methodologies adopted. This is due to the fact that many students have difficulty accessing classes in these new formats imposed by the situation. Therefore, this calamity brought about emotional instability with intense and lasting repercussions. This segment of the population will need great emotional support and an effective therapeutic plan to stabilize the mental health of each sick person, ensuring effective and continuous therapeutic assistance for university students.